Real Convergence and Integration - Aurel Iancu (Romanian Journal of European Affairs)
The study is based on the critical observations that competitive market forces alone are not able to assure convergence with the developed countries. These observations are grounded on the results of the computation of the marginal rate of return to capital (which contradict the neoclassical model hypotheses), as well as on the real process of polarisation of the economic activities, taking place worldwide and in accordance with the law of competition. Unlike those who trust the perfect competitive market virtues, the EU’s economic policy is realistic as it is based on the harmonisation of the market forces with an economic policy based on the principle of cohesion, which supports, by means of economic levers, the less developed regions and member countries. This paper deals with the evolution of the EU cohesion funds, as well as with the results of convergence.